THE VALUE OF AUTOPSY IN MEDICAL EDUCATION: STUDENT'S ATTITUDES & OPINION - Altaf Pervez Qasim; Khalid Ur Rehman Hashmi et al. (Journal of University Medical & Dental College, 2015)
ABSTRACT: BACKGROUND: The autopsy has been regarded as a valuable adjunct to undergraduate medical education. Autopsy as an educational experience helps the students to correlate clinical ﬁndings with basic medical sciences. However, they might be somewhat less willing to consent an autopsy on themselves or their own relatives. It is important to get the views of medical students in relation to its relevance in medical education and to justify the continuous inclusion of autopsy in medical curriculum. OBJECTIVE: To determine the thoughts, feelings & attitude of medical students towards autopsy & its value in medical education. SETTING & DURATION OF STUDY: Study was conducted in Punjab Medical College, Faisalabad during academic years 2011 & 2012. STUDY DESIGN: Cross Sectional Study. MATERIAL & METHODS: Self-administered Questionnaire was distributed among 250 students rd thof 3 & 4 year MBBS classes who had completed the course of Forensic Medicine & ﬁnished their tenure in Postmortem Unit. They were asked to respond anonymously to a set of questions concerned with the thoughts and feelings of autopsy, death & grief as well as their views on the importance of autopsy to medical education, reactions to the ﬁrst autopsy they watched, attitude towards having autopsy performed on themselves or any relative and inﬂuence of autopsy on specialization in the subject of Forensic Medicine & Toxicology. RESULTS: Out of 210 respondents, 140 (66.67%) were female while 70 (33.33%) were males. Most of the students 188 (89.52%) agreed on the importance of autopsy in medical education and 158 (75.23%) suggested that medical students should observe and participate in more autopsies. The majority 193 (91.90%) students felt that autopsy should not be scrapped from the medical curriculum. Fifty (23.80%) respondents would not mind autopsy being performed on themselves and their relatives. Only a few students agreed to specialize in Forensic Medicine of whom 6 (2.82%) were females and 14 (6.66%) were males. Forty three students don't want to specialize in this subject because it is dirty procedure & deals with death, while ﬁfty respondents would rather specialize in some other ﬁeld. Nineteen students felt that Forensic Medicine is not lucrative. Eighty Six (47.77%) students were uncomfortable on the ﬁrst day in the autopsy room compared to 114 (63.33%) who remained comfortable. CONCLUSION: The exposure of students to autopsy is important to their medical education. The knowledge of medicolegal autopsy will broaden the student's perceptive and will help the legal system in delivering quick justice in criminal cases. A variety of emotional reactions were conveyed by the students towards experience of watching autopsies but the procedure was acceptable to majority and they recommended watching autopsy for all medical students. The autopsies being important teaching tool should be revived and carefully adjusted in the programmes designed to teach the students as part of the medical curriculum about death and its process. The students should be provided opportunities to attend autopsy demonstrations and presentations on the utility of autopsies during the clinicopathological meetings of that hospital